BEĞAVÎ'NİN MEÂLİMÜ'T-TENZÎL İSİMLİ TEFSİRİNDEKİ HADİSLERİN TAHRİÇ VE DEĞERLENDİRİLMESİ (AL-İ İMRÂN SÛRESİ 121-200. AYETLER) - KILIÇ, YAKUP (Fırat Üniveristesi, 2018)
Müfessir, muhaddis ve aynı zamanda büyük bir fakîh olan Beğavî'nin, Meâlimü't-Tenzîl isimli eseri, tefsir alanında otorite kabul edilen bir kaynaktır. Beğavî bu eserini rivâyet metoduna göre yazmış ve iyi bir hadisçi olması hasebiyle ayetlerin tefsirinde sıkça hadis kullanmıştır. Çalışmamızda Beğavî hakkında bilgi verdikten sonra Beğavî'nin tefsir alanında kaleme almış olduğu Meâlimü't Tenzîl isimli eserinde Âl-i İmrân sûresinin (121-200. Ayetler) tefsirinde yer alan 77 Hadisin tahricini yaptık. Tahricini yaptığımız hadislerin sıhhati hakkında muhaddis münekkidlerin görüşlerini de dikkate alarak sıhhat değerlendirmesinde bulunduk. Beğavî'nin ayetlerin tefsiri bağlamında kullanmış olduğu hadisler hakkında şunları söyleyebiliriz: Hadislerin 55'i sahîh, 9'u hasen, 8'i zayıf, 1'i ise mevzû'dur. Hadislerin 4'ünün sıhhati hakkında ise hüküm verilememiştir. Beğavî'nin kullanmış olduğu hadislerin çoğunluğu (% 83.11) sahîh rivâyetlerden oluşmaktadır. Zayıf hadislerin tüm hadislere oranı ise ancak % 10.38'dir. Hasen hadislerin tüm hadislere oranı, % 11.68; mevzû hadislerin oranı da % 1.29'dur. Hakkında hüküm verilemeyenlerin oranı ise % 5.19'dur. Bu hadislerin 58 tanesi Kütüb-i Tis'ada, 8'i diğer hadis kaynaklarında, 10 tanesi ise hadis kaynakları dışındaki eserlerde geçmektedir. Anahtar Kelimeler: Beğavî, Meâlimü't-Tenzîl, Hadis, Kütüb-i Tis'a, Kütüb-i Sitte, Tahrîc, Âl-i İmrân.

Maâlim at-Tanzil, the most famous work of al-Baghawi, who is a scholar of tafsir, hadith and fiqh is a source regarded as an authority in the scope of tafsir. Al-Baghawi used riwaya (narrative reports) method while writing this work and proved his mastership in the field of hadith. While explaining Qur'anic verses, Baghawi used hadiths as he was also a scholar of hadith. This study aims, after giving information about Baghawi, to verify seventy-seven of hadiths from the tafsir of surah Al 'Imran (the verses between 121 and 200) in Maâlim at-Tanzil, the tafsir of al-Baghawi. With this respect, we have evaluated the authenticity of the hadiths we have extracted by considering the views of critics who are scholar of hadith. We can assert the following about the hadiths which Baghawi used in order to explain the Qur'anic verses: Out of seventy-seven hadiths we have studied, fifty-five of them are sound (sahîh), nine of them are good (hasan), eight of them are weak (da'if), and one of them are fabricated (mawdu'). Four of the hadiths are not adjudicated. Most of the hadiths which are used by Baghawi consist of sound (sahîh) narrations 83.11%. The proportion of weak (da'if) hadiths to all hadiths the author used is only 10.38%. The proportion of the good hadiths is 11.68%, and the fabricated hadiths is 1.29%. The proportion of all hadiths which can not be adjudicated ise 5.19%. Out of these seventy-seven hadiths used by the author, fifty-eight of them are quoted from al-Kutub at-Tis'ah, eight of them are found in the other hadith sources, and ten of them are found in the sources other than hadith. Only one of the hadiths are from the narrations that we could not find their sources. Key Words: al-Baghawi, Ma'alim at-Tanzil, Hadith, al-Kutub at-Tis'ah, Extraction, surah Al'Imran, al-Kutub at Sıtteh.
The extraction and evaluation of hadiths in the commentary of al-Baghawi titled Maalim at-tanzil (Between 121 th and 200th verses of surah Al-i İmran)
Keywords: Din